PERAN KNOWLEDGE SHARING BEHAVIOUR DALAM MENINGKATKAN KUALITAS LAYANAN PUBLIK DIKANTOR LURAH BORONGLOE KABUPATEN GOWA - Syailia, Nurul Fidyah; R, Muh Nur; Achsanuddin, A ndi Nur (Yayasan Nuraini Ibrahim Mandiri, 2024)
This research is a type of qualitative research with the aim of knowing exactly the role of knowledge sharing behavior in improving the quality of public services at the Borongloe Village Head Office, Gowa Regency. The type of data used is descriptive qualitative with data collection through observation and interviews. The research results that can be written show that the role of knowladge sharing plays an important role for borongloe village head employees in improving the quality of services provided to the community. It is said to play an important role because seen from the dimensions of knowledge sharing and service quality, researchers found that there are four indications that can affect it, namely knowladge donating (knowledge transfer), knowladge collection (knowledge collection), technical quality (what is obtained from services), and functional quality (how to get services). Although the role of knowledge sharing for employees is not optimal, they still prioritize integrity by continuing to provide excellent service